Uso da onda ultra-sônica como meio de controle do processo de secagem da madeira - Calegari, Leandro (2006)
The purpose of this study is to explore the use of ultrasonic technique in order to estimate the moisture content during wood drying, from green condition to the end of the drying process. The treatments were based on the combination of two different species (Pinus elliottii Engelm. and Eucalyptus grandis Hill ex Maiden), drying temperatures (20, 40 and 70ºC) and transducers types (plane faces and dry points). The experiment was set up according to a factorial model, with approximately 50 replications. A 50 kHz - transducer (PUNDIT ultrasonic equipment) was used. Samples tested had nominal 3.5 cm thick by 10 cm wide by 25 cm long and the ultrasonic wave speed propagation was measured according to its longitudinal direction. The results indicated increase of ultrasonic speed with reduction of moisture content for both transducers used. This relationship is valid for the wood from green to the end of the drying process. However, low correlation was observed, and the best model adjusted determination coefficients were observed with eucalypt wood (Raj.²= 88%). The use of the transducers of dry points was more practical than the plane faces one. Moreover, they should be used in hard and not much heterogeneous woods. The ultrasonic velocity was also influenced by wood density and drying temperature. The species showed different effects of wood density on the velocity. In the pine wood, velocity increased with increasing density. Opposing effect was observed in eucalypt wood. The ultrasonic speed tended to decrease as drying temperature increased. Nevertheless, this variable s influence was reduced. It was not noticed any defined influence of the species in the ultrasonic speed when the plane face transducers were used. However, the eucalyptus wood provided larger velocity when the dry point transducers were used. The results suggest that this method presents good potential for the control of the drying process. Studies on the influence of the several wood characteristics on the ultrasonic wave s velocity and the development of specific transducers for the use of this alternative in commercial scale are required.